Foundations of Psychology: An Introductory Text - Nicky Hayes (New York Routledge, 1994)
A comprehensive introduction to the fundamental principles, theories and research in modern psychology. This textbook is written for students by an experienced psychologist, lecturer and examiner and covers the core areas of psychology: cognitive; individual differences and abnormal psychology; physiological; social; developmental; and comparative. It presents contemporary issues and classic studies in a critical framework and traces the development of ideas and methods in psychology. This is designed for all psychology students, including undergraduates, A level students and others on pre-degree courses. Nicky Hayes is the author of "A First Course in Psycholoy", and "Psychology: An Introduction" with Sue Orre.
Includes Colored Illustrations, Glossary, Bibliography and index
Keywords: Psychology